2000
DOI: 10.1128/mcb.20.15.5722-5735.2000
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Histone Acetyltransferase Activity through Interaction of Epstein-Barr Nuclear Antigen 3C with Prothymosin Alpha

Abstract: The Epstein-Barr virus (EBV) nuclear antigen 3C (EBNA3C) is essential for EBV-dependent immortalization of human primary B lymphocytes. Genetic analysis indicated that amino acids 365 to 992 are important for EBV-mediated immortalization of B lymphocytes. We demonstrate that this region of EBNA3C critical for immortalization interacts with prothymosin alpha (ProT␣), a cellular protein previously identified to be important for cell division and proliferation. This interaction maps to a region downstream of amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
107
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 87 publications
4
107
1
Order By: Relevance
“…As mentioned above, PT␣ has been reported to interact with CBP, Epstein-Barr virus nuclear antigen 3C, and p300 (37)(38)(39)(40). These results indicate that PT␣ is a coactivator of transcriptional activation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As mentioned above, PT␣ has been reported to interact with CBP, Epstein-Barr virus nuclear antigen 3C, and p300 (37)(38)(39)(40). These results indicate that PT␣ is a coactivator of transcriptional activation.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, it has been reported that PT␣ interacts with CBP and enhances the transcriptional potential of CBP (37). In addition, PT␣ interacts with the Epstein-Barr virus nuclear antigen 3C and p300, and cooperatively regulates the acetylation (38,39) and deacetylation (40) of histones. Moreover, PT␣ selectively enhances the transcriptional activity of the estrogen receptor (ER) but not the transcriptional activity of other nuclear receptors (41).…”
mentioning
confidence: 99%
“…ProT␣ is a small ubiquitous protein, generally abundant, and present both in nucleus and cytoplasm. It is involved in the proliferation of mammalian cells (19), in transcription (20), in chromatin remodeling, and in protection against apoptosis (22). The molecular mechanisms are unknown, except for the antiapoptotic activity of ProT␣, which occurs through inhibition of apoptosome formation (22).…”
Section: Effect Of P8 and Prot␣ Knockdown On Staurosporine-induced Cellmentioning
confidence: 99%
“…ProT␣ was associated with cellular proliferation and carcinogenesis (18,19), cellular and viral transcription (19,20), and remodeling of chromatin (21). More recently, ProT␣ was shown to inhibit caspase 9 activation by blocking apoptosome formation, which prevents the activation of effector caspases (22) p8 and ProT␣ are two small proteins without stable secondary structure in solution, showing opposite electrostatic charges at neutral pH.…”
mentioning
confidence: 99%
“…Indeed, all mutations in EBNA3A or EBNA3C that inhibit association with RBPJ are null for LCL growth (22)(23)(24), whereas EBNA3A or EBNA3C mutations that affect binding to the adenovirus E1a C-terminal binding protein (CtBP) corepressor result in continuous, albeit slower, growth (22)(23)(24)(25)(26). EBNA3C or EBNA3A have many specific and potentially significant interactions with other transcription factors or modifiers, including PU.1, Spi-B, HDAC1, DP103, prothymosin-α, p300, Nm23-H1, SUMO1, and SUMO3, cyclin A, SCF SKP2 ubiquitin ligase, pRb, Chk2, Mdm2, and MRS18-2, and these interactions could be relevant to CDKN2A p16 INK4A or p14 ARF regulation and LCL growth (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Furthermore, EBNA3C upregulates TCL1A and ITGA4, down-regulates JAG1 and NCALD RNAs, and cooperates with EBNA3A in repressing Bim, a proapoptotic Bcl-2 family protein (24,(39)(40)(41).…”
mentioning
confidence: 99%